Efektifitas Program CSR Hidroponik Rakit Apung Terhadap Peningkatan Taraf Hidup Penerima Manfaat Program: - - Hilmy, Sigit Irfan; Poetri, Izmi Dwi Maharani; Putri, Bella Adinda (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
A company, in implementing a CSR program, aims to meet the needs of the community as beneficiaries of the CSR program. However, in practice, the expected results are often not obtained so that the main objectives of the program are not achieved. Program Hidroponik Rakit Apung in Kelurahan Mariana and LPP Kelas II A Palembang aims to increase people's income through hydroponic vegetable agribusiness. But then another problem arose. Hydroponic installations that use pipes as planting media are quite expensive. Starting from seeds, installation of pipes, rockwool, planting media, nutrition, and so on. So that an innovation emerged, namely the application of Hidroponik Rakit Apung using styrofoam. This then raises the question of the effectiveness of its implementation in improving the living standards of program beneficiaries. This research found that the Hidroponik Rakit Apung community development program had an impact on the energy efficiency of 109.8 KwH, emission reduction of 0.97722 Ton Co2eq, water efficiency of 300 liters, and utilization of Non-B3 waste of 21.6 kg. If assessed from the economic side, the saving value from energy use efficiency is Rp. 734,391, and the saving value from water use efficiency is Rp. 6,840. Based on the results obtained, the replacement of hydroponic installations that originally used pipes, to later become floating rafts or used Styrofoam, is considered effective and can improve people's lives.